Progress in Cell Cycle Research 1997
DOI: 10.1007/978-1-4615-5371-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 (“casein kinase-2”) and its implication in cell division and proliferation

Abstract: Protein kinase CK2 (also termed casein kinase-2 or -IT) is a ubiquitous Ser/Thr-specific protein kinase required for viability and for cell cycle progression. CK2 is especially elevated in proliferating tissues, either normal or transformed, and the expression of its catalytic subunit in transgenic mice is causative of lymphomas. CK2 is highly pleiotropic: more than 160 proteins phosphorylated by it at sites specified by multiple acidic residues are known. Despite its heterotetrameric structure generally compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
280
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 317 publications
(289 citation statements)
references
References 190 publications
(168 reference statements)
7
280
0
2
Order By: Relevance
“…Inhibition of phosphorylation, for example in the presence of DRB, would allow hydroxylation and inhibit HIF-1 activity. Two-hybrid screening in yeast has shown that CK2b has several binding partners, among them the collagen a-prolyl-4 hydroxylase, 58,59 but the mechanisms of their interaction as well as the functional consequence of the interaction are currently poorly understood, as is the question of whether CK2 would also interact with the HIF prolyl hydroxylase. The use of antibodies that could recognize the hydroxylated N803 would be helpful to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of phosphorylation, for example in the presence of DRB, would allow hydroxylation and inhibit HIF-1 activity. Two-hybrid screening in yeast has shown that CK2b has several binding partners, among them the collagen a-prolyl-4 hydroxylase, 58,59 but the mechanisms of their interaction as well as the functional consequence of the interaction are currently poorly understood, as is the question of whether CK2 would also interact with the HIF prolyl hydroxylase. The use of antibodies that could recognize the hydroxylated N803 would be helpful to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few functions have been proposed : for example, an involvement in anti-apoptotic pathways [26] or in the cellular resistance to oxidative stress exploited by the combined superoxide dismutase activity and copperbinding capacity of PrP c [27,28]. Our results disclose another possible function of PrP, by showing that bPrP interacts with and up-regulates one of the most pleiotropic protein kinases, CK2, known to impinge on many proteins implicated in a variety of cell functions, in particular in signal transduction and gene expression pathways [1,8,29]. It is noteworthy that CK2 is also widely exploited by infectious agents, such as viruses and parasites, to perform the phosphorylation of proteins essential to their life cycle [29].…”
Section: Discussionmentioning
confidence: 63%
“…Protein kinase CK2 (an acronym derived from the misnomer ' casein kinase-2 ') is probably the most pleiotropic member of the huge family of protein kinases [1]. The long list of its substrates includes at least 200 proteins that share a phosphoacceptor site specified by multiple negatively charged amino acids [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CKII activity increases when quiescent cells are stimulated to proliferate (Issinger, 1993;Allende and Allende, 1995;Pinna and Meggio, 1997). Studies performed using selective inhibitors also illustrate that CKII is required during various stages of cell cycle progression (Ford et al, 2000).…”
Section: Ckii Inhibitors Suppress Proliferation Of U87 Astroglioma Cellsmentioning
confidence: 97%
“…It exists as a constitutively active tetramer that contains two catalytic subunits, or ' (37-44 kDa), and two regulatory subunits (24-28 kDa) (Allende and Allende, 1995;Pinna and Meggio, 1997;Litchfield, 2002). The two catalytic subunits are highly homologous, but the ' subunit has a unique required role in spermatogenesis (Xu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%